Legal Protection for Consumers for Drug SalesDiet without Distribution License Through Marketplace - Halimah Tussya'dyah; M. Zamroni M. Zamroni (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This paper aims to explain the legal protection of consumers for the sale of diet drugs without a distribution permit through the marketplace. This research is a normative legal research. The type of approach used in this study is the statutory approach and the conceptual approach. The collection of legal material in this study used the snowball technique as used in empirical research. The analysis of legal material in this research is to use descriptive, comparative, evaluative and argumentative analysis. This study aims to answer the problem of what are the permit provisions for diet drugs sold through marketplaces? Then how about the legal protection for consumers who buy diet drugs without a distribution permit through the marketplace? After conducting the research, it can be concluded that business actors who trade diet/slimming products without a distribution permit are actions that are prohibited for business actors, so these goods must be withdrawn from circulation. Then,